Experimental Study on UHPC-Based Grouting Materials and Mechanical Performance of Grouted Splice Sleeve Joints - Fu, Tao; Hou, Jianpu; Zhu, Zhixin; Meng, Lingxiao; Sun, Zhonghua; Wang, Kai; Ren, Xiaoqian (Frontiers in Materials, 2022)
The prefabricated concrete structure is regarded as the main body of the green construction technology, while the joint connection of the prefabricated components is the weak link of force. In addition, the grouting sleeve connection is a widely used connection method in the prefabricated component joints. The effective anchorage of reinforcement is realized by the implementation of a mechanical bite force, friction force and bonding force between reinforcement, grouting material and sleeve inner wall, respectively. Along these lines, in this work, a UHPC-based grouting material was prepared, and its main technical performance was tested. The influence of the grouting mix proportion and anchorage length on the stress performance was thoroughly investigated by carrying out a unidirectional tension test of eight grout-filled splice sleeves. The acquired results show that UHPC grouting containing micro and particles possess high mechanical strength and durability. The incorporation of UHPC grouting containing steel fibers can further improve the compressive and flexural strength. However, its fluidity will be reduced and grouting difficulties will be induced. For that reason, the utilization of UHPC-based grouting material without steel fibers is recommended. The grout-filled splice sleeve joints with UHPC meet also the strength requirements, and the sleeve can be found in the elastic stage in the test, indicating that sleeve joints possess a higher safety margin.